Detemir plus aspart and glulisine induced lipoatrophy: 2015 literature review and report of a new case. Issue 1 (December 2015) - Saberi, Sima; Esfandiari, Nazanene; MacEachern, Mark; Tan, Meng
Abstract Background In the first and only literature review, conducted in 2009, of human insulin analog- induced lipoatrophy, there were 12 published cases, including 1 with aspart, 1 with detemir, 1 with NovoMix 30 and none with detemir plus aspart. It is perceived that insulin analog induced-lipoatrophy is increasing. We conducted a 2015 literature review of published reports of lipoatrophy induced by aspart, detemir, detemir plus aspart, and NovoMix30. We also report a new case of detemir plus aspart and glulisine induced lipoatrophy. Methods Our focused literature searches (limited to 1995–2014) in PubMed, Embase, and Web of Science, using a combination of insulin analog and lipoatrophy terminology, was conducted in early January 2015. Results From the 520 unique citations there were 33 (from 13 papers and 9 abstracts) lipoatrophy cases induced by detemir (n = 5), aspart (n = 21), detemir plus aspart (n = 4) and NovoMix 30 (n = 3), representing 30 new cases since 2009. Many of these reported cases were females (76 %), had type 1 diabetes mellitus (T1DM) (94 %) and were in young persons (61 %). A 41-year-old T1DM woman developed lipoatrophy on her upper thighs, arms and abdomen 14 months after injecting detemir plus aspart at the same sites. Later on, after a year on continuous subcutaneous insulin infusion (CSII) using aspart and then glulisine, she developed lipoatrophy at the infusion sites. When CSII insulin was switched to lispro she did not develop lipoatrophy after 10 months. Meanwhile, the original lipoatrophy sites significantly improved. Conclusions Our literature review uncovered 30 new published cases of aspart, detemir, aspart plus detemir and NovoMix 30-induced lipoatrophy since 2009. The largest increase in cases was in aspart- induced lipoatrophy. Recent surveys showed most rapid acting insulin analog-induced lipoatrophy were associated with CSII. In our review of the reported cases, 85.7 % cases of aspart-induced lipoatrophy were associated with CSII. As in previous reports, we showed lipoatrophy was more common in females, T1DM and young persons. Our patient may be the 5th published case of detemir plus aspart-induced lipoatrophy and possibly the first case report of glulisine induced lipoatrophy. She believed both detemir plus aspart and glulisine induced the lipoatrophy.